Configuration Design and Performance Evaluation of Deep-Sea Self-Powered Power Generation Devices based on High-Voltage Thermoelectric Materials - Fan, Chongwen (Scientific Journal of Technology, 2025)
Aiming at the energy bottleneck of long-term operation of deep-sea equipment, this paper proposes a high-voltage self-powered power generation device with new Ag₁.₉₉₅Au₀.₀₀₅Te₀.₇S₀.₃ nano-thermoelectric materials as the core. Through Au doping and Te/S ratio control, the ZT value of the material reaches 1.2 at 300 K, and the thermal conductivity of the lattice decreases below 0.4 W/m·K; Adopt TA32 titanium alloy shell+vacuum potting +Inconel 718 metal seal to realize 30 MPa pressure resistance. Trapezoidal array layout and micro-channel water cooling design make the thermal efficiency of the system reach 85%, and the output power density is 320 W/m² and the conversion efficiency is 8.5% under the temperature difference of 10 K deep sea, which is 407% and 124% higher than that of the traditional Bi₂Te₃ system respectively. Integrating 1850 kWh Ferrous lithium phosphate energy storage and SiC inverter, the end-to-end energy utilization rate of 72 h system is 7.8%. After 500 h aging in 30 MPa and 3.5% NaCl environment, the power attenuation is only 4.7%, which verifies the stability and engineering application potential of the device under extreme conditions in deep sea.